Electric Bass Solo Performance in the Repertoire: Spain - Mahendra, Yogi; Munafri, Sastra; Herdianto, Ferry; Hendri, Yon (Institut Seni Indonesia Padangpanjang, 2024)
This performance is a performance by an electric bass soloist who presents a repertoire entitled: spain, a technical approach applied in preparing to play the instrument, namely the Extreme Slap Bass etude guide: A Dictionary Of Grooves. The aim of this solo performance is to be able to present a repertoire of electric bass instruments through a technical approach based on applicable scientific principles. The resulting repertoire performance was 7 minutes long, presented at the Hoerijah Adam ISI Padangpanjang performance building. The solo performance was presented with a big band formation. The application of the technique to the Spanish repertoire uses electric bass instruments, and a slap technique approach that applies the etude Extreme Slap Bass: A Dictionary Of Grooves.